Pengaruh Kualitas Pelayanan dan Kepercayaan terhadap Loyalitas Pelanggan dengan Kepuasan Pelanggan sebagai Variabel Intervening pada Gojek di Yogyakarta - Septia Lorensia; Nonik Kusuma Ningrum (Universitas Batanghari Jambi, 2023)
Based on this research aims to determine the effect of service quality, trust on customer satisfaction. And to determine the effect of service quality and trust on customer loyalty. This research uses quantitative research methods or surveys. The sampling technique was purposive sampling in which 130 respondents were taken from Gojek customers in Yogyakarta. To test the quality of the data using the validity test, reliability with data analysis techniques descriptive analysis, classic assumption test, normality test, heteroscedasticity test, and multicollinearity test with multiple linear regression analysis tests. Testing the hypothesis by using the partial test (t test) and the coefficient of determination (R2) and the F test and Sobel test. The results showed that the variable Service Quality has a positive and insignificant effect on customer satisfaction. Trust has a positive and significant effect on customer satisfaction. Service quality has a positive and insignificant effect on customer loyalty. Trust Has a positive and significant effect on customer loyalty. Customer satisfaction has a positive and significant effect on customer loyalty.